1998
DOI: 10.1038/sj.mp.4000443
|View full text |Cite
|
Sign up to set email alerts
|

Linkage analysis of putative schizophrenia gene candidate regions on chromosomes 3p, 5q, 6p, 8p, 20p and 22q in a population-based sampled Finnish family set

Abstract: During the past decade numerous studies have been published describing chromosomal regions potentially linked with schizophrenia. Unfortunately, none of these studies has been able to conclusively identify any specific gene that predisposes to schizophrenia. Typically evidence for linkage is seen on large chromosomal regions, as expected, containing tens or even hundreds of genes. Furthermore, attempts to replicate the findings have rarely been successful leaving a confusion about the existence of predisposing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 36 publications
(39 reference statements)
2
41
0
1
Order By: Relevance
“…67 Even with large sample sizes, and a gene conferring a sixfold increased risk to sibs, if one confines the search to the region of maximal sharing, the gene will be missed over 60% of the time. 68 Hovatta and colleagues noted 69 considerable error in the position of the maximum lod scores, especially for sample sizes of 100 or 200 sib pairs and for the less significant findings. We have also examined this issue by simulation.…”
Section: Discussionmentioning
confidence: 99%
“…67 Even with large sample sizes, and a gene conferring a sixfold increased risk to sibs, if one confines the search to the region of maximal sharing, the gene will be missed over 60% of the time. 68 Hovatta and colleagues noted 69 considerable error in the position of the maximum lod scores, especially for sample sizes of 100 or 200 sib pairs and for the less significant findings. We have also examined this issue by simulation.…”
Section: Discussionmentioning
confidence: 99%
“…The COMT enzyme has two forms, a soluble form (S-form) and a membrane-bound form (M-form), with the latter mainly expressed in brain. 1 The COMT gene is located on chromosome 22q11, a region that showed positive results in some linkage studies [2][3][4] but was negative in others. [5][6][7][8] The region is also associated with the velocardiofacial syndrome (VCFS), 9 a genetic disorder characterized by cleft palate, heart defects and characteristic facial appearance.…”
mentioning
confidence: 99%
“…This result was not subsequently replicated in a large multicenter study, the Schizophrenia Linkage Collaborative Group III (SLCG III) which included the Irish cohort [86]. Weakly positive results were seen nearby on 5q 33.1 in a Finnish cohort of 62 multiplex families, with a twopoint LOD score of 1.36 at the CSF1R locus [87]. This was subsequently supported by a LOD score > 3 in an extended group of 237 Finnish families [88], though these results on 5q22-31 were somewhat proximal to the original findings on 5q33.1.…”
Section: Chromosomementioning
confidence: 97%
“…Twin studies have also been used in biometric studies to determine the most likely disease model. Cardno and colleagues performed such an analysis on pooled twin data and found that a model containing additive genetic and environmental effects gave the best fit, with a heritability of 83% (95% CI [74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] and specific environmental effects of 17% (95% CI 10-26) [13]. Discordant MZ twin studies have also shown that the children of both affected and unaffected MZ twins have similar risks of schizophrenia-like psychosis [14].…”
Section: Evidence For a Genetic Basismentioning
confidence: 99%